Analytical control of drinking water in Piedmont: some results (2008-2012) - Zicari, Giuseppe; Marro, Silvia; Panata, Marisa; Soardo, Vincenzo; Berruti, Renza; Maggi, Claudio; Cerrato, Elena; Ferrari, Romina; Gulino, Margherita (Progress in Nutrition, 2014)
Background: The Italian national regulations, to verify the suitability of water intended for human consumption, require the monitoring of a concentration of about 70 chemical, physical and microbiological parameters. In Piedmont, where 4,357,663 residents are divided into 1,207 municipalities (2012), analytical monitoring is implemented by 12 local health authorities in collaboration with the laboratories of the Regional Agency for Environmental Protection. Objectives: We present the results of monitoring the quality of water intended for human consumption implemented by the Health Service and other information provided by the Managers of the water service. Methods: The official results of the analytical control of water intended for human consumption are recorded in Regional Health Service databases. These databases also collect information on the managers of the water service and the characteristics of the distribution network. Results: Most of the 2,222 water networks in Piedmont can serve up to 500 people and less than 40 networks could provide a sufficient quantity of water to meet all regional households demands. The Local Health Authorities make at least 21,000 samples of water per year, by some of the 8,478 sites selected for sampling, mainly in the terminal part of the distribution network. In the years 2008-2012, it have been implemented 790,306 analytical determinations about 74 different parameters, including 23 residues of plant protection products. The highest fraction of non-compliant parameters, taken over by some local health authorities, was equal to 2% of the researches which were carried out. Among the parameters that do not comply, it should be noted: coliform bacteria at 37°C, Clostridium perfringens, Escherichia coli, aluminum, arsenic, iron, manganese, nitrates and sulfates; atrazine, bentazone, desethylatrazine, metolachlor and terbuthylazine. Conclusions and recommendations: The management of the analytical control officer provides annual regional planning that could be improved by making it more flexible and adaptable to different local contexts.